Identification Of KOLB’S Learning Style In Seventh Grade Students and The Effect On Misconception In Science Learning - Fitria Izza Tazkiah; Sri Mulyani; Sentot Budi Rahardjo (JETL (Journal of Education, Teaching and Learning), 2021)
The purpose of this study is to identify Kolb’s learning style of seventh-grade students. Learning style is a combination of the way how the student absorbs then processes the information. Kolb's learning style, developed by David Kolb, combines students' learning tendency and produces four learning styles; they are diverger, assimilator, converger, and accommodator. Learning style is one of the factors can cause misconceptions. A misconception is a difference between a student's conceptions and the expert. Usually, the concepts are difficult to correct. This misconception will affect a student's achievement and disturb in understanding and developing a student's knowledge. The method applied in this study was a survey method with describtive qualitative technique. The data were collected using Kolb's Learning Style Inventory (KLSI) 3.1 version. The subjects were 78 students in three schools with high, medium, and low grades The results indicated that from 78 students, there were 40 divergers (51%), 12 assimilators (15%), ten convergers (13%), and 16 accommodators (21%). Each kind of learning style affects a student's misconception. This research benefits in identifying misconceptions probably faced by students in certain subjects of science learning.